Electrolyte and energy storage device

By adding additive A containing naphthyl, acid anhydride and nitro to the electrolyte of the lithium-ion battery, a stable SEI membrane structure is formed, which solves the problem of short cycle life of the lithium-ion battery and achieves higher cycle stability and Capacity retention rate.

CN119447461AActive Publication Date: 2025-02-14XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411649930.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The cycle life of existing lithium-ion batteries is relatively short, and how to develop lithium-ion batteries with long cycle life is still an urgent problem to be solved.

Method used

By adding an additive A with a structure containing naphthyl, anhydride and nitro to the electrolyte solution, a solid electrolyte interface (SEI) membrane structure with an inner layer inorganic and outer layer organic is formed, thereby improving the stability and interface impedance of the SEI film and reducing the Side reactions.

Benefits of technology

It significantly improves the cycle stability and capacity retention rate of lithium-ion batteries, extends the cycle life of lithium-ion batteries, and improves the cycle performance and energy efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447461A_ABST
    Figure CN119447461A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and an energy storage device, the electrolyte comprises an additive A, the structural formula of the additive A simultaneously comprises naphthyl, anhydride and nitro, the naphthyl is a substituent represented by a chemical formula 1, the anhydride is a substituent represented by a chemical formula 2, and the nitro is a substituent represented by a chemical formula 3; chemical formula 1: # imgabs 0 # chemical formula 2: # imgabs 1 # chemical formula 3: # imgabs 2 # wherein R1, R2 and R3 are each independently selected from any one of carbon atoms at positions 1-8 in naphthyl. According to the electrolyte provided by the invention, the capacity retention ratio of the energy storage device after circulation can be improved, so that the cycle life of the energy storage device can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of energy storage devices, and in particular to an electrolyte and an energy storage device. Background Art

[0002] As energy storage devices such as lithium-ion batteries are widely used in new energy vehicles, mobile communications and other fields, people have put forward higher requirements for the cycle life of energy storage devices. At present, the main methods to improve the cycle life of lithium-ion batteries include optimizing the composition and structure of electrode materials, optimizing the composition of electrolytes, and optimizing the manufacturing process of batteries. Although the existing technology can improve the cycle life of lithium-ion batteries to a certain extent, there are still some problems and limitations. How to develop lithium-ion batteries with long cycle life is still an urgent problem to be solved. Summary of the invention

[0003] The purpose of the embodiments of the present application is to provide an electrolyte and an energy storage device. Using the electrolyte can improve the capacity retention rate of the energy storage device after cycling, thereby improving the cycle life of the energy storage device.

[0004] The embodiment of the present application provides an electrolyte, the electrolyte includes an additive A, the structural formula of the additive A includes a naphthyl group, an acid anhydride group, and a nitro group, the naphthyl group is a substituent represented by Chemical Formula 1, the acid anhydride group is a substituent represented by Chemical Formula 2, and the nitro group is a substituent represented by Chemical Formula 3;

[0005]

[0006] Wherein, R1, R2 and R3 are each independently selected from any carbon atom in positions 1 to 8 of the naphthyl group.

[0007] In the electrolyte provided in the embodiment of the present application, the structural formula of the additive A added contains the functional groups of naphthyl, anhydride and nitro at the same time. During the operation of the energy storage device formed by assembling the electrolyte, the nitro functional group in the additive A can undergo a reduction reaction to generate Li3N, LiN x O y The anhydride functional group can react to form an SEI (Solid Electrolyte Interphase) film of inorganic components such as RCO2Li. In addition, the naphthyl functional group can also promote the electron cloud conjugation of additive A and increase the reduction potential of the additive A molecule. At the same time, the rigid structure of the naphthyl group can improve the stability of the SEI film structure. The electrolyte formed by additive A can generate an SEI film structure with an inner inorganic layer and an outer organic layer. The SEI film structure has high stability, which is beneficial to stabilizing the interface of the negative electrode plate and reducing side reactions, thereby improving the cycle stability and capacity retention rate of the energy storage device, and then helping to improve the cycle life of the energy storage device and the construction of a long-life energy storage device.

[0008] In addition, the nitro group in the structural formula of additive A can generate an SEI film containing lithium nitride. Since lithium nitride has a relatively high electrical conductivity, the interfacial impedance of the formed SEI film is relatively small, so that the polarization of the battery assembled with the electrolyte containing additive A is relatively small, which is beneficial to improve the performance of the energy storage device, such as cycle performance and energy efficiency. Compared with the nitro functional group, using other functional groups such as fluorine functional groups to replace the naphthyl group will generate an SEI film containing lithium fluoride. The electrical conductivity of lithium fluoride is relatively low, which will make the interfacial impedance of the formed SEI film relatively large, thereby reducing the performance of the assembled energy storage device.

[0009] In one possible embodiment, R1 is selected from the carbon atom at position 1 of the naphthyl group, and R2 is selected from the carbon atom at position 8 of the naphthyl group. In the structure of additive A, the anhydride functional group is connected to the two benzene rings of the naphthyl group at the same time, so that the structure of additive A has a high degree of electronic conjugation, which is beneficial to improving the reduction and decomposition ability of additive A, thereby facilitating the formation of a more stable SEI film formed during the operation of the energy storage device.

[0010] In one possible embodiment, the additive A is selected from at least one of the structural formulas (I-1) to (I-12):

[0011]

[0012] In a possible embodiment, the electrolyte further includes a cyclic carbonate solvent. The anhydride group is also a reducing functional group. When a part of the anhydride functional group generates the organic SEI component RCO2Li, another part of the anhydride functional group can also undergo a reduction reaction to generate O - and C· free radicals, and initiate the ring-opening polymerization of cyclic carbonate solvents such as ethylene carbonate (EC) to generate polycarbonate SEI components, which can further improve the stability of the SEI film, further improve the stability of the interface of the negative electrode plate, reduce side reactions, and thus help improve the cycle stability and capacity retention rate of the energy storage device, thereby helping to improve the cycle life of the energy storage device and facilitate the construction of a long-life energy storage device.

[0013] In one possible implementation, the cyclic carbonate solvent is selected from at least one of ethylene carbonate and propylene carbonate.

[0014] In a possible implementation, the mass fraction of additive A is 0.01% to 5% based on the mass of the electrolyte. When the content of additive A in the electrolyte is too small, the effect of additive A is not obvious, and the optimization effect on improving the stability of the SEI film is not obvious. When the content of additive A in the electrolyte is too high, the interface impedance of the SEI film will increase, which is not very helpful for improving the performance of the energy storage device. By controlling the mass fraction of additive A to 0.01% to 5%, it is helpful to ensure that the assembled energy storage device has a higher cycle life.

[0015] In a possible implementation manner, the mass fraction of additive A is 0.2% to 1%.

[0016] An embodiment of the present application further provides an energy storage device, which includes a negative electrode plate and the electrolyte as described above, wherein the electrolyte infiltrates at least a portion of the negative electrode plate.

[0017] In a possible implementation, the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes any one of artificial graphite, natural graphite, soft carbon, hard carbon, lithium metal, sodium metal, silicon, silicon carbon or silicon oxygen material.

[0018] In a possible implementation, the energy storage device includes any one of a lithium-ion battery and a sodium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 dQ / dV curve of a lithium-graphite button cell formed by assembling the electrolyte of Comparative Example 1 and the electrolyte of Example 1. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0022] The embodiment of the present application provides an energy storage device, which includes, by way of example, but is not limited to, any one of a lithium-ion battery and a sodium-ion battery, wherein the lithium-ion battery may be a lithium-ion hard-shell battery, a lithium-ion soft-pack battery, or a lithium-ion button battery.

[0023] Take the structure of the energy storage device including a shell, a battery cell and an electrolyte as an example. Specifically, the battery cell is installed on the inner side of the shell, and the electrolyte is injected into the inner side of the shell and soaks the battery cell.

[0024] The battery cell includes a positive electrode sheet, a separator, a negative electrode sheet, a positive electrode ear and a negative electrode ear. The separator is located between the positive electrode sheet and the negative electrode sheet, the positive electrode ear is electrically connected to the positive electrode sheet, and the negative electrode ear is electrically connected to the negative electrode sheet. Exemplarily, the positive electrode sheet, the separator, and the negative electrode sheet can be stacked in sequence, wound to form a bare battery cell, and then the positive electrode ear and the negative electrode ear are welded to prepare the battery cell.

[0025] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer covering the surface of the positive electrode current collector. Exemplarily, the positive electrode current collector is aluminum foil. The positive electrode material layer includes materials such as positive electrode active materials and additives. Exemplarily, the positive electrode active material is lithium iron phosphate. The additives in the positive electrode material layer include conductive agents and adhesives. Exemplarily, the conductive agent is conductive carbon black SP (Super P), and the adhesive is polyvinylidene fluoride (PVDF).

[0026] The diaphragm can adopt an existing battery diaphragm. Exemplarily, the diaphragm is a polypropylene (PP) film. The negative electrode plate includes a negative electrode current collector and a negative electrode active layer coated on the surface of the negative electrode current collector. Exemplarily, the negative electrode current collector is a copper foil. The negative electrode active layer includes materials such as negative electrode active materials and additives. Exemplarily, the negative electrode active material includes any one of artificial graphite, natural graphite, soft carbon, hard carbon, lithium metal, sodium metal, silicon, silicon carbon or silicon oxygen material. Among them, the additives in the negative electrode active layer include materials such as conductive agents, thickeners, and adhesives. Exemplarily, the conductive agent is conductive carbon black SP (SuperP), the thickener is carboxymethyl cellulose (Carboxymethyl Cellulose, CMC), and the adhesive is styrene butadiene rubber (Polymerized Styrene Butadiene Rubber, SBR) or asphalt.

[0027] The electrolyte infiltrates at least a portion of the negative electrode sheet and at least a portion of the positive electrode sheet to achieve electrolyte infiltration of the battery cell. The electrolyte includes a solvent, a lithium salt and an additive A. Exemplarily, the solvent includes a cyclic carbonate solvent. Exemplarily, the cyclic carbonate solvent is selected from at least one of ethylene carbonate (EC) and propylene carbonate (PC). It is understandable that the solvent also includes other types of solvents such as chain carbonate solvents. Exemplarily, the chain carbonate solvent can be ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. Exemplarily, the lithium salt can be lithium hexafluorophosphate (LiPF6).

[0028] The structural formula of the additive A includes a naphthyl group, an acid anhydride group, and a nitro group at the same time, the naphthyl group is a substituent group represented by Chemical Formula 1, the acid anhydride group is a substituent group represented by Chemical Formula 2, and the nitro group is a substituent group represented by Chemical Formula 3;

[0029]

[0030] Wherein, R1, R2 and R3 are each independently selected from any carbon atom in positions 1 to 8 of the naphthyl group.

[0031] The structural formula of the additive A contains naphthyl, anhydride and nitro functional groups. During the operation of the energy storage device formed by the electrolyte assembly, the nitro functional group in the additive A is a reducing functional group, which can undergo a reduction reaction to generate Li3N, LiN x O y The anhydride functional group can react to form an SEI film of organic components such as RCO2Li. In addition, the naphthyl functional group can also promote the electron cloud conjugation of additive A and increase the reduction potential of the additive A molecule. At the same time, the rigid structure of the naphthyl group can improve the stability of the SEI film structure. The electrolyte formed by additive A can generate an inner inorganic and outer organic SEI film structure. The SEI film structure has high stability, which is beneficial to stabilize the interface of the negative electrode plate and reduce side reactions, thereby improving the cycle stability and capacity retention rate of the energy storage device, thereby improving the cycle life of the energy storage device and facilitating the construction of a long-life energy storage device.

[0032] Among them, the process of the anhydride functional group reacting to generate the RCO2Li organic component is:

[0033]

[0034] In addition, the nitro group in the structural formula of additive A can generate an SEI film containing lithium nitride. Since lithium nitride has a relatively high electrical conductivity, the interfacial impedance of the formed SEI film is relatively small, so that the polarization of the battery assembled with the electrolyte containing additive A is relatively small, which is beneficial to improve the performance of the energy storage device, such as cycle performance and energy efficiency. Compared with the nitro functional group, using other functional groups such as fluorine functional groups to replace the naphthyl group will generate an SEI film containing lithium fluoride. The electrical conductivity of lithium fluoride is relatively low, which will make the interfacial impedance of the formed SEI film relatively large, thereby reducing the performance of the assembled energy storage device.

[0035] In addition, the anhydride group is also a reducing functional group. When one part of the anhydride functional group generates the organic SEI component RCO2Li, the other part of the anhydride functional group can also undergo a reduction reaction to generate O - and C· free radicals, and initiate the ring-opening polymerization of cyclic carbonate solvents such as ethylene carbonate (EC) to generate polycarbonate SEI components, which can further improve the stability of the SEI film, further improve the stability of the interface of the negative electrode plate, reduce side reactions, and thus help improve the cycle stability and capacity retention rate of the energy storage device, thereby helping to improve the cycle life of the energy storage device and facilitate the construction of a long-life energy storage device.

[0036] Exemplarily, the additive A is selected from at least one of the structural formulas (I-1) to (I-12):

[0037]

[0038] Exemplarily, R1 is selected from the carbon atom at position 1 in the naphthyl group, R2 is selected from the carbon atom at position 8 in the naphthyl group, and R3 can be selected from the carbon atom at position 5 (or carbon atom at position 4) in the naphthyl group, and the structural formula of additive A is the above structural formula (I-1). R1 ​​is selected from the carbon atom at position 1 in the naphthyl group, and R2 is selected from the carbon atom at position 6 (or carbon atom at position 3) in the naphthyl group, and the structural formula of additive A is the above structural formula (I-2). R1 ​​is selected from the carbon atom at position 1 in the naphthyl group, and R2 is selected from the carbon atom at position 7 (or carbon atom at position 2) in the naphthyl group, and the structural formula of additive A is the above structural formula (I-3).

[0039] In the structural formula of the above-mentioned additive A, when R1 is selected from the carbon atom at position 1 in the naphthyl group, and R2 is selected from the carbon atom at position 8 in the naphthyl group, the anhydride functional group in the structure of the additive A is simultaneously connected to the two benzene rings of the naphthyl group, so that the degree of electronic conjugation in the structure of the additive A is high, which is beneficial to improving the reduction and decomposition ability of the additive A, thereby facilitating the formation of the SEI (Solid Electrolyte Interphase) film formed during the operation of the energy storage device to be more stable.

[0040] Exemplarily, when R1 is selected from the carbon atom at position 7 in the naphthyl group, R2 is selected from the carbon atom at position 8 in the naphthyl group, and R3 is selected from the carbon atom at position 6, carbon atom at position 5, carbon atom at position 4, carbon atom at position 3, carbon atom at position 2 and carbon atom at position 1 in the naphthyl group, the additive A of the above-mentioned structural formula (Ⅰ-4), structural formula (Ⅰ-5), structural formula (Ⅰ-6), structural formula (Ⅰ-7), structural formula (Ⅰ-8) and structural formula (Ⅰ-9) are formed respectively.

[0041] Exemplarily, when R1 is selected from the carbon atom at position 6 of the naphthyl group, R2 is selected from the carbon atom at position 7 of the naphthyl group, and R3 is selected from the carbon atom at position 5 (or carbon atom at position 8), carbon atom at position 4 (or carbon atom at position 1) and carbon atom at position 3 (or carbon atom at position 2) of the naphthyl group, additives A of the above-mentioned structural formulas (Ⅰ-10), (Ⅰ-11) and (Ⅰ-12) are formed respectively.

[0042] Among them, exemplary, based on the mass of the electrolyte, the mass fraction of additive A is 0.01% to 5%, that is, the mass fraction of additive A in the electrolyte is 0.01% to 5%. Specifically, the mass fraction of additive A can be 0.01%, 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, and other values, as well as any value between the above values. When the content of additive A in the electrolyte is too small, the effect of additive A is not obvious, and the optimization effect on improving the stability of the SEI film is not obvious. When the content of additive A in the electrolyte is too high, the interface impedance of the SEI film will increase, which will not help much to improve the performance of the energy storage device. By controlling the mass fraction of additive A to 0.01% to 5%, it is beneficial to ensure that the assembled energy storage device has a higher cycle life. In some other embodiments, based on the mass of the electrolyte, the mass fraction of additive A is 0.2% to 1%.

[0043] Taking additive A of structural formula (I-1) as an example, the reduction potential and test of additive A of structural formula (I-1) are performed. The specific test method is as follows: lithium-ion button batteries are assembled using the electrolyte of comparative example 1 without additive A and the electrolyte of embodiment 1 containing additive A, and then the lithium-ion button batteries are discharged at a constant current of 0.05 mA at 25°C to obtain a differential capacity (dQ / dV) curve of the discharge process, and the reduction potential of additive A of structural formula (I-1) is identified based on this dQ / dV curve.

[0044] Wherein, the lithium ion button cell is prepared according to the following steps:

[0045] Preparation of electrolyte: First, the electrolyte lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) to obtain 100g of basic electrolyte. In the mixed solvent, the mass ratio of EC, EMC and DMC was 1:1:2. Among them, the electrolyte of comparative example 1 was the basic electrolyte. 0.2% of additive A was added to the basic electrolyte to obtain the electrolyte of Example 1.

[0046] Preparation of negative electrode sheet: Take the negative electrode active material graphite, conductive carbon SP, thickener CMC, binder SBR and asphalt and disperse them in deionized water according to the ratio and mix them evenly to obtain negative electrode slurry. Apply the negative electrode slurry on the negative electrode current collector copper foil. The coating weight of the negative electrode slurry is 144mg / 1540.25mm 2 After drying, cold pressing, slitting and cutting, the negative electrode sheet is obtained. Among them, the negative electrode slurry is coated to form the negative electrode active layer.

[0047] Preparation of diaphragm: A polypropylene (PP) film with a thickness of 16 μm was used as the diaphragm.

[0048] Preparation of lithium-ion button cells: Assemble lithium-graphite button cells using graphite negative electrode sheets, separators, lithium metal discs and electrolytes.

[0049] The dQ / dV curve of the lithium-graphite button cell formed by assembling the electrolyte of Comparative Example 1 and the electrolyte of Example 1 is as follows: Figure 1 shown. Figure 1 The dQ / dV curves shown in the figure show that the additive A in the electrolyte of Example 1 has a multi-step reduction reaction. + When the nitro functional group in additive A is reduced to form Li3N and LiN x O y The SEI film with inorganic components is at a potential of 2.27V vs.Li / Li +When about , the anhydride functional group in additive A is reduced to generate O- and C· free radicals, and initiates the ring-opening polymerization of cyclic carbonate solvent ethylene carbonate (EC) to generate the SEI film of organic components. In addition, the anhydride group can also react to generate the SEI film of organic components of RCO2Li. Therefore, by using additive A containing both nitro functional groups and anhydride functional groups, an inner layer inorganic and outer layer organic SEI structure can be formed, and the SEI structure stability is relatively high. In addition, the naphthyl functional group in additive A can also promote electron cloud conjugation, increase the reduction potential of the molecule, and the rigid structure of naphthalene can improve the stability of the SEI structure. Experimental results show that the embodiment of the present application can form a SEI structure with higher structural stability by adding additive A in the electrolyte, which helps to stabilize the graphite negative electrode interface, reduce side reactions, and effectively improve the cycle stability and capacity retention rate of the assembled battery, thereby realizing the construction of a long-life lithium-ion battery.

[0050] The performance of the energy storage device formed by assembling the electrolyte containing the additive A is studied below through specific examples 1-36 and comparative example 1. Among them, examples 1-36 and comparative example 1 both provide an energy storage device, the energy storage device is exemplified by a lithium-ion battery, the positive electrode sheet in the energy storage device is exemplified by a lithium iron phosphate positive electrode sheet, and the negative electrode sheet is exemplified by a graphite negative electrode sheet, and is specifically prepared according to the following steps:

[0051] Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate, conductive carbon black SP, and binder PVDF are dispersed in a solvent NMP (N-Methylpyrrolidone) at a mass ratio of 90:5:5 and mixed evenly to obtain positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the coating weight of the positive electrode slurry is 300mg / 1540.25mm 2 After drying, cold pressing, slitting and cutting, the positive electrode sheet is obtained. Among them, the positive electrode slurry is coated to form the positive electrode active layer.

[0052] Preparation of negative electrode sheet: Disperse the negative electrode active material graphite, conductive carbon SP, thickener CMC, and binder SBR in a mass ratio of 96:1:1.5:1.5 in deionized water and mix them evenly to obtain negative electrode slurry. Apply the negative electrode slurry on the negative electrode current collector copper foil. The coating weight of the negative electrode slurry is 144mg / 1540.25mm 2 After drying, cold pressing, slitting and cutting, the negative electrode sheet is obtained. Among them, the negative electrode slurry is coated to form the negative electrode active layer.

[0053] Preparation of electrolyte: First, the electrolyte lithium hexafluorophosphate (LiPF6) is dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) to obtain 100g of a basic electrolyte. In the mixed solvent, the mass ratio of EC, EMC and DMC is 1:1:2. The electrolyte of comparative example 1 is the basic electrolyte. Additive A in different amounts is added to the basic electrolyte to obtain the electrolytes of Examples 1-40.

[0054] Preparation of diaphragm: A polypropylene (PP) film with a thickness of 16 μm was used as the diaphragm.

[0055] Preparation of lithium-ion soft pack batteries:

[0056] The prepared lithium iron phosphate positive electrode sheet, separator, and graphite negative electrode sheet are stacked in order so that the separator is located in the middle of the positive and negative electrodes to separate the positive electrode sheet from the negative electrode sheet. After winding, a bare battery cell is obtained. After welding the pole ears, the battery cell is assembled into a casing, and after injecting the prepared electrolyte, the battery cell is packaged, allowed to stand, formed, shaped, and capacity tested, etc., to finally prepare a lithium-ion battery.

[0057] Among them, in the lithium ion batteries of Examples 1-40 and Comparative Example 1, the type and content of additive A in the electrolyte are shown in Table 1. The lithium ion batteries of Examples 1-40 and Comparative Example 1 were respectively measured for the capacity retention rate of 1000 cycles at 25°C and 0.5P constant power and the capacity retention rate of 1000 cycles at 45°C and 1P constant power, and the results are shown in Table 1.

[0058] Capacity retention rate test of 1000 cycles at 25°C and 0.5P: The test temperature is 25°C, the lithium-ion battery is charged at a constant power of 0.5P to a charging cut-off voltage of 3.65V, the initial charging capacity is recorded, and the lithium-ion battery is left to stand for 10 minutes, the lithium-ion battery is discharged at a constant power of 0.5P to a discharge cut-off voltage of 2.5V, and the discharge capacity of the lithium-ion battery is recorded. Capacity retention rate of 1000 cycles at 25°C = (discharge capacity after the 1000th cycle / discharge capacity of the first cycle) × 100%.

[0059] Capacity retention rate test of 1000 cycles at 45°C and 1P: The test temperature is 45°C, the lithium-ion battery is charged at a constant power of 1P to a charging cut-off voltage of 3.65V, the initial charging capacity is recorded, and the lithium-ion battery is left to stand for 10 minutes, the lithium-ion battery is discharged at a constant power of 1P to a discharge cut-off voltage of 2.5V, and the discharge capacity of the lithium-ion battery is recorded. Capacity retention rate of 1000 cycles at 45°C = (discharge capacity after the 1000th cycle / discharge capacity of the first cycle) × 100%.

[0060] Among them, P refers to the rated charging or discharging power of the battery, and its value is the nominal voltage U of the battery multiplied by the current density of 1C. The nominal voltage of the iron phosphate battery is 3.2V, and 0.5P refers to 0.5 times the rated power.

[0061] Table 1 Type, content of additive A and performance of lithium ion battery in Examples 1-40 and Comparative Example 1

[0062]

[0063]

[0064] As can be seen from Table 1, the electrolyte of Comparative Example 1 does not contain additive A, but is only a simple carbonate mixed solvent system. The capacity retention rate of the assembled lithium-ion battery after 1000 cycles at room temperature 25°C is 61%, and the capacity retention rate after 1000 cycles at high temperature 45°C is 55%. The capacity retention rate of the lithium-ion battery of Comparative Example 1 after cycles at room temperature 25°C and high temperature 45°C is low, and the cycle life of the lithium-ion battery of Comparative Example 1 is low. By comparing Examples 1-40 and Comparative Example 1, additive A is added to the electrolytes of Examples 1-40 of the present application, and the capacity retention rate of the lithium-ion battery formed by the electrolyte assembly of Examples 1-36 after 1000 cycles at room temperature 25°C is approximately 65% ​​to 94%, and the capacity retention rate after 1000 cycles at high temperature 45°C is approximately 60% to 90%. The cycle performance of the lithium-ion battery of Examples 1-40 at room temperature 25°C and high temperature 45°C has been improved. The experimental results show that by adding additive A to the electrolyte, the capacity retention rate of the assembled lithium-ion battery after cycling at room temperature and high temperature can be effectively improved, thereby helping to improve the cycle life of the lithium-ion battery.

[0065] In addition, by comparing Examples 3-7 and Examples 1-2, as the content of additive A increases, the capacity retention of the energy storage device of Examples 1-7 after cycling first gradually increases, and then gradually decreases. Among them, the content of additive A in the electrolyte of Example 1 is low, and the cycle performance of the assembled energy storage device is improved compared with the energy storage device of Comparative Example 1, but the increase is small. The content of additive A in the electrolyte of Example 2 is too high, and the cycle performance of the assembled energy storage device is improved compared with the energy storage device of Comparative Example 1, but the increase is small. Through a large number of experimental studies, the present application has found that controlling the mass fraction of additive A in the electrolyte to 0.01% to 5% can significantly improve the capacity retention rate of lithium-ion batteries after normal temperature and high temperature cycling, thereby facilitating the improvement of the cycle life of lithium-ion batteries. Furthermore, the mass fraction of additive A in the electrolyte is controlled to be 0.2% to 1%, and the assembled lithium-ion battery has a higher capacity retention rate after normal temperature and high temperature cycling, and the lithium-ion battery has a longer cycle life.

[0066] By comparing Examples 5-13 with Examples 14-40, taking the mass fraction of additive A in the electrolyte as 0.2% as an example, the lithium ion battery (Example 5, Example 8 and Example 11) formed by assembling the electrolyte with additive A of structural formula (I-1) to structural formula (I-3) has a capacity retention rate of approximately 87% to 89% after 1000 cycles at room temperature 25°C, and a capacity retention rate of approximately 79% to 81% after 1000 cycles at high temperature 45°C. The lithium ion battery assembled by the electrolyte with additive A of structural formula (I-4) to structural formula (I-12) has a capacity retention rate of approximately 79% to 83% after 1000 cycles at room temperature 25°C, and a capacity retention rate of approximately 71% to 76% after 1000 cycles at high temperature 45°C, which is lower than the lithium ion battery assembled by the electrolyte with additive A of structural formula (I-1) to structural formula (I-3).

[0067] The experimental results show that when the content of additive A in the electrolyte is the same, additive A of structural formula (I-1) to structural formula (I-3) is added to the electrolyte of Examples 5-13, and the capacity retention rate of the assembled lithium ion batteries after cycling at room temperature 25°C and high temperature 45°C is better than that of the lithium ion batteries of Examples 14-40. This is because in additive A of structural formula (I-1) to structural formula (I-3), the anhydride functional group is connected to the two benzene rings of the naphthyl group at the same time, so that the degree of electronic conjugation in the structure of additive A is high, and the reduction and decomposition ability of additive A is stronger, so that the film formation of the formed SEI film is more stable, which can further improve the capacity retention rate of the assembled battery after cycling, which is conducive to improving the cycle life of the lithium ion battery.

[0068] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte includes an additive A, wherein the structural formula of the additive A includes a naphthyl group, an acid anhydride group, and a nitro group, wherein the naphthyl group is a substituent represented by Chemical Formula 1, the acid anhydride group is a substituent represented by Chemical Formula 2, and the nitro group is a substituent represented by Chemical Formula 3; Chemical formula 1: Chemical formula 2: Chemical formula 3: Wherein, R1, R2 and R3 are each independently selected from any carbon atom in positions 1 to 8 of the naphthyl group.

2. The electrolyte according to claim 1, characterized in that R1 is selected from the carbon atom at position 1 of the naphthyl group, and R2 is selected from the carbon atom at position 8 of the naphthyl group.

3. The electrolyte according to claim 1, characterized in that The additive A is selected from at least one of the structural formulas (I-1) to (I-12):

4. The electrolyte according to any one of claims 1 to 3, characterized in that The electrolyte also includes a cyclic carbonate solvent.

5. The electrolyte according to claim 4, characterized in that The cyclic carbonate solvent is selected from at least one of ethylene carbonate and propylene carbonate.

6. The electrolyte according to any one of claims 1 to 3, characterized in that Based on the mass of the electrolyte, the mass fraction of the additive A is 0.01% to 5%.

7. The electrolyte according to claim 6, characterized in that Based on the mass of the electrolyte, the mass fraction of the additive A is 0.2% to 1%.

8. An energy storage device, characterized in that: The energy storage device comprises a negative electrode plate and an electrolyte as claimed in any one of claims 1 to 7, wherein the electrolyte infiltrates at least a portion of the negative electrode plate.

9. The energy storage device according to claim 8, characterized in that: The negative electrode plate includes a negative electrode active material, and the negative electrode active material includes any one of artificial graphite, natural graphite, soft carbon, hard carbon, lithium metal, sodium metal, silicon, silicon carbon or silicon oxygen material.

10. The energy storage device according to claim 8, characterized in that: The energy storage device includes any one of a lithium ion battery and a sodium ion battery.

Citation Information

Patent Citations

  • Electrolyte additive and electrolyte and lithium ion battery containing same

    CN101673852A

  • Lithium ion battery and electrolyte thereof

    CN109428117A

  • Electrolyte and electrochemical device comprising same

    CN114221036A

  • Electrolyte for lithium ion secondary battery and lithium ion secondary battery

    CN117039144A

  • Electrolyte solution and secondary battery using same

    US20170162910A1